“If everything goes well, I’ll become a teacher!”: Reflections on art education and being an art educator in contemporary times (Revista Apotheke, 2025)
This article focuses on issues related to education, teaching and art education. Would it be possible to reconcile to be artist and to be teacher? What aspects bring art and education closer together? To answer these questions, we aim to investigate the professional, social and political characteristics intrinsic to art education, identifying overlaps and differences between the work of teachers and artists. To this end, we developed a bibliographical research based on theoretical and methodological contributions from art educators. Structurally, we first investigated the accounts that the Brazilian artist Antonio Carlos Rodrigues (1948 --), better known as Tuneu, makes in relation to his experience as an apprentice and as an art educator. We emphasize the convergences and divergences between being an artist and being an art educator. In the second moment, we seek to analyze historically how the intersections between artistic practice and the exercise of teaching are elaborated, above all, in the pedagogical trends consolidated in contemporary times. In our final considerations, we arrive at art education as a possible alternative to the trends that until now subsidize the teaching of Art in Brazil.
Keywords: Education; Teacher Training; Art teaching; Visual Art; Cultural Studies